Fever, Irritability, and Ulcerations in an Infant. Issue 6 (26th September 2012) - Patel, Devika; Cook, Nathan; Newell, Brandon; Becker, Mara
<x xml:space="preserve">Abstract</x> Abstract: A young infant with fever and oral ulcerations is presented herein. Extensive infectious, nutritional, immunodeficiency and autoimmune work up was performed. Pertinent maternal history suggested the potential diagnosis of neonatal Behçet's, and treatment for this condition resulted in rapid and sustained clinical improvement.